Feasibility study of genetic algorithms application for implementation of block cryptosystem cryptanalysis - Yury O. Chernyshev; Alexander S. Sergeyev; Nikolay N. Ventsov; Alexander N. Ryazanov (Advanced Engineering Research)
Feasibility of genetic search algorithms application for implementation of the cryptanalysis of block cipher methods is considered. A distinctive feature of the bioinspired cryptanalysis methods application (in particular, genetic methods) is the possibility of using the encryption (or decryption) algorithm as an objective function for the suitability evaluation of the key defined by genetic operations. Consequently, when using the bioinspired cryptanalysis methods, the S key definition (for example, when using type 2 cryptanalysis) depends not so much on the complexity of the ciphering transformations, as on the bioinspired method which is to provide a sufficient variety of key generation that shows the significance of the research task of the bioinspired algorithms feasibility (in particular, genetic search methods) for the block cryptosystem cryptanalysis. It is noted also that as the distinctive feature of both block cipher methods, and the genetic algorithms is their internal parallelism, then the task of developing a cryptanalysis algorithm based on the parallel implementation of the constituent stages is relevant. An algorithm of the block methods cryptanalysis on the example of the DES standard on the basis of its parallel version is offered; the experiment results of the quasioptimal key determination obtained at the parallel algorithm implementation on the 8-letter text blocks are given. It is noted that time costs of the algorithm realization do not exceed the time of the known cryptanalysis implementation.